SmartPLS for the human resources field to evaluate a model - Sander, Tom; Teh, Phoey Lee * (2014)
This paper describes the Partial Least Square model to test the robustness and value of the statistical evaluation. The test is to evaluate the fit of the model for a small sample. The statistical data is calculated with the SmartPLS software. SmartPLS is a tool created for statistical analysis, namely PLS – SEM (Structural Equation Model). The paper describes the advantages and disadvantages of SmartPLS and provides an argument for the use of SmartPLS in the scientific world. At the moment the use of SmartPLS in science concentrates mainly in the information technology field and the marketing area. The authors describe the use of SmartPLS for the human resources area which is a new field for SmartPLS software. The paper further describes the validity and reliability for PLS – SEM.